Four-in-One stimulus-responsive long-lived luminescent systems based on pyrene-doped amorphous polymers - Wang, Zhonghao (2022)
Materials exhibiting ultralong luminescent lifetime show promising applications in the fields of information encryption, sensing, and bioimaging. Herein, we present a low-cost and general strategy to achieve stimulus-responsive ultralong organic phosphorescence (UOP) based on pyrene chromophores doped into polymer matrices. The UOP of the resulted systems presents radiation-, concentration-, time-, and excitation-dependent characteristics. The UOP color can be turned from blue to red by changing the excitation wavelength or the concentration of chromophores. Experimental results prove that these characteristics are attributed to the consumption of triplet oxygen and the different aggregation states of chromophores in the polymer matrices. Finally, we demonstrate that these systems could be applied for multilevel information encryption. This work would promote further development of multi-responsive long-lived luminescent materials.